Biomechanical analysis of spinal cord injury during scoliosis correction surgery - Wang, Haimei; Zhang, Chunyu; Wang, Yongqiang; Zeng, Yan; Chen, Songhao; Su, Xingyu; Li, Weishi; Yu, Miao; Chen, Duanduan (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Surgical correction is a common treatment for severe scoliosis. Due to the significant spinal deformation that occurs with this condition, spinal cord injuries during corrective surgery can occur, sometimes leading to paralysis. Methods: Such events are associated with biomechanical changes in the spinal cord during surgery, however, their underlying mechanisms are not well understood. Six patient-specific cases of scoliosis either with or without spinal complications were examined. Finite element analyses (FEA) were performed to assess the dynamic changes and stress distribution of spinal cords after surgical correction. The FEA method is a numerical technique that simplifies problem solving by replacing complex problem solving with simplified numerical computations. Results: In four patients with poor prognosis, there was a concentration of stress in the spinal cord. The predicted spinal cord injury areas in this study were consistent with the clinical manifestations of the patients. In two patients with good prognosis, the stress distribution in the spinal cord models was uniform, and they showed no abnormal clinical manifestations postoperatively. Discussion: This study identified a potential biomechanical mechanism of spinal cord injury caused by surgical correction of scoliosis. Numerical prediction of postoperative spinal cord stress distribution might improve surgical planning and avoid complications.